First report of chromosome and karyological analysis of Gekko nutaphandi (Gekkonidae, Squamata) from Thailand: Neo-diploid chromosome number in genus Gekko - Thongnetr W. (2023)
The karyotypes of red-eyed Gecko are not reported yet. Herein, we describe the karyotypes of red-eyed Gecko (Gekko nutaphandi Bauer, Sumontha & Pauwels, 2008) from Thailand. Gecko chromosome preparations were directly conducted from bone marrow and testis. Chromosomal characteristics were analyzed by Giemsa stain-ing, Ag-NOR banding as well as fluorescence in situ hybridization (FISH) using micro-satellites d(GC)15 probe. The results showed that the number of diploid chromosomes is 2n=34, while the fundamental number (NF) is 46 in both males and females. The types of chromosomes were 4 large metacentric, 6 large submetacentric, 2 medium telocentric, 2 small metacentric and 20 small telocentric chromosomes. The results of conventional Giemsa staining presented the diploid chromosome number differentiation even in the same genus. NORs are located at the secondary constriction to the tel-omere on the long arm of chromosome pair 5. There are no sex differences in karyo-types between males and females. FISH with d(GC)15 sequences were also displayed at the telomeres of most other chromosomes. We found that during metaphase I the homologous chromosomes showed synapsis, which can be defined as 19 ring bivalents and 17 haploid chromosomes (n=17) at metaphase II as a diploid species. The karyo-type formula is as follows: 2n (34) = L4m+L6 sm +M2t+S2m+S20t.